Peran E-Commerce dalam Menggerakkan Konsumsi Nasional dan PDRB Indonesia pada Tahun 2024 - Wiondy, Vanessa Anastasya; Riyanto, Evelyn Valerie; Wijaya, Felicia Devina; Feodora, Ellen (Accounting Study Program, Universitas Ciputra Surabaya, 2026)
The evolution of e-commerce in Indonesia has shown quite rapid expansion in line with advances in digital technology and the growing use of the internet. E-commerce usage is found on various platforms that provide various conveniences for people to conduct transactions, thus bringing about structural changes in household consumption patterns, which are the largest component of the Gross Regional Domestic Product (GRDP) of provinces in Indonesia. This study was conducted to investigate the effect of the number of e-commerce businesses and determine the amount of household consumption on the GRDP of provinces in Indonesia. In addition, the research method used is quantitative by utilizing secondary data from the Central Statistics Agency (BPS). The data analysis used multiple linear regression supported by classical assumption tests to investigate the feasibility of this study. The analysis demonstrates that the number of e-commerce businesses has a significant positive effect on the GRDP of provinces in Indonesia, while household consumption has a positive but insignificant effect on GRDP. Individually, household consumption has a dominant effect on GRDP, and the number of e-commerce businesses also contributes to increasing trade and economic digitalization in each region. These findings confirm that the evolution of e-commerce supported by increasing public purchasing power plays a significant role in driving regional economic growth. The findings of this research are expected to offer implications for local governments in formulating digital economic development policies and strategies for increasing regional economic growth.